2018
DOI: 10.1037/dec0000073
|View full text |Cite
|
Sign up to set email alerts
|

Rejecting outliers: Surprising changes do not always improve belief updating.

Abstract: An important human skill is the ability to update one's beliefs when they are no longer supported by the environment. Current models of dynamic decision-making suggest that more unexpected, or "surprising," events lead to quicker belief updating. The current article tests the ubiquity of the notion that surprising environmental changes are always positively related to updating. Using a novel task based on the game Plinko, we tracked participants' beliefs as they learned distributions of ball drops. At an unann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 18 publications
1
13
0
Order By: Relevance
“…Interestingly, the latter account appears to be consistent with the evidence (Filipowicz et al, 2018): human participants learn effectively in mean-shift paradigms, while they adapt less rapidly in variance-shifts paradigms.…”
Section: Antecedents Of Reference-model Based Learningsupporting
confidence: 80%
“…Interestingly, the latter account appears to be consistent with the evidence (Filipowicz et al, 2018): human participants learn effectively in mean-shift paradigms, while they adapt less rapidly in variance-shifts paradigms.…”
Section: Antecedents Of Reference-model Based Learningsupporting
confidence: 80%
“…In line with the ViolEx model (Gollwitzer et al, 2018;Rief & Glombiewski, 2016), higher levels of immunization were associated with higher achievement expectations in the negativefeedback condition. However, this effect was lost over the successive disconfirmations, indicating that it was easier to immunize one's expectations against a single disconfirming event than against a series of expectation disconfirmations (see also Filipowicz et al, 2018). The data from the last trial with negative feedback even indicated that, in the long run, higher initial immunization may be related to stronger expectation change, which probably demonstrates that the sum of the otherwise gradual expectation change is condensed after realizing that one has to take the expectation violations seriously.…”
Section: Discussionmentioning
confidence: 99%
“…Most available research on effects of immunization, assimilation, and accommodation (and related concepts) on expectation change has been conducted with adults. With regard to the processes suggested to contribute to the persistence of expectations, this research focused on immunization rather than assimilation (e. g., Filipowicz et al, 2018;Kube et al, 2018 </litr>;Roese & Sherman, 2007).…”
Section: Associations Of the Violex Processes With Expectation Changementioning
confidence: 99%
“…Beyond such negligible expectation violations, the "delta rule" predicts that higher magnitudes of expectation violations will result in higher magnitudes of expectation change, a facet of accommodation (Rescorla & Wagner, 1972). However, when expectation violations become extremely large, beyond some threshold, individuals may engage in subtyping (i.e., immunization) and categorize their experiences as exceptions to the rule (Filipowicz et al, 2018;Summerfield & Tsetsos, 2015). This suggests that the relationship between expectation violation magnitude and probability of accommodation may follow an inverted U-shape (Filipowicz et al, 2018) rather than a monotonously increasing function.…”
Section: Influences On Responding With Accommodation or Immunizationmentioning
confidence: 99%
“…However, when expectation violations become extremely large, beyond some threshold, individuals may engage in subtyping (i.e., immunization) and categorize their experiences as exceptions to the rule (Filipowicz et al, 2018;Summerfield & Tsetsos, 2015). This suggests that the relationship between expectation violation magnitude and probability of accommodation may follow an inverted U-shape (Filipowicz et al, 2018) rather than a monotonously increasing function. In addition to the magnitude, the direction of expectation violation may influence cognitive responses, for instance, in optimism biases with stronger immunization tendencies for unpleasant compared to pleasant expectation violations (Garrett & Sharot, 2017;Sharot et al, 2011).…”
Section: Influences On Responding With Accommodation or Immunizationmentioning
confidence: 99%